(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Sports games are based on human-specific play activities. The game plays a big role in human life. In childhood, play is an effective means of basic activity, preparation for life, work, physical education. Sports-related games fall into a separate group, based on competition - sports games or recreational sports. The characteristics of sports games are determined by the specific characteristics of the competitive activity that distinguishes them from other sports.